2017
DOI: 10.1093/mnras/stx258
|View full text |Cite
|
Sign up to set email alerts
|

Lensing is low: cosmology, galaxy formation or new physics?

Abstract: We present high signal-to-noise galaxy-galaxy lensing measurements of the BOSS CMASS sample using 250 square degrees of weak lensing data from CFHTLenS and CS82. We compare this signal with predictions from mock catalogs trained to match observables including the stellar mass function and the projected and two dimensional clustering of CMASS. We show that the clustering of CMASS, together with standard models of the galaxy-halo connection, robustly predicts a lensing signal that is 20-40% larger than observed.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
301
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 230 publications
(346 citation statements)
references
References 192 publications
(330 reference statements)
37
301
5
3
Order By: Relevance
“…Here Ωm and σ8 are, respectively, the present matter density in units of the critical density, and the root-meansquare (rms) of the linear density fluctuations smoothed on scale of 8h −1 Mpc. The KiDS-450 constraints are in agreement with other cosmic shear studies Joudaki et al 2017a;Troxel et al 2017), galaxy-galaxy lensing (Leauthaud et al 2017), and pre-Planck CMB constraints (Calabrese et al 2017). Understanding such a tension is currently an important aspect of research in the field.…”
supporting
confidence: 87%
“…Here Ωm and σ8 are, respectively, the present matter density in units of the critical density, and the root-meansquare (rms) of the linear density fluctuations smoothed on scale of 8h −1 Mpc. The KiDS-450 constraints are in agreement with other cosmic shear studies Joudaki et al 2017a;Troxel et al 2017), galaxy-galaxy lensing (Leauthaud et al 2017), and pre-Planck CMB constraints (Calabrese et al 2017). Understanding such a tension is currently an important aspect of research in the field.…”
supporting
confidence: 87%
“…Various works have found levels of stochasticity that are broadly consistent, using a range of samples and scales in numerical simulations [e.g., [83,84]] and data [e.g., [85][86][87][88][89][90]]. The comparison of lowz galaxy clustering and galaxy-galaxy lensing in DES SV on scales above 4h −1 comoving Mpc provided similar hints of r < 1 ( [91,92], see also [93]).…”
Section: A Results On Bias and Stochasticitymentioning
confidence: 58%
“…Outside DES, other studies have also examined potential differences between clustering and lensing. In particular, in [81] the authors perform a galaxy-galaxy lensing measurement around BOSS CMASS spectroscopic galaxies using data from the CFHTLenS and SDSS Stripe 82 surveys, and find the lensing signal to be lower than that expected from the clustering of lens galaxies and predictions from standard models of the galaxy-halo connection. In this study, as expressed in the r values reported above, and more broadly in the DES Y1 cosmological analysis presented in [25], we find the clustering and lensing signals to be consistent within our uncertainties, though we note that the [81] analysis was done on significantly smaller scales.…”
Section: Redmagic Galaxy Biasmentioning
confidence: 99%